Explain how to simplify this complex fraction. 330pages/3/4hour.

Answers

Answer 1
Answer: Answer:
= 330/1 ÷ 3/4

= (330 × 4) / (3 × 1)

= 1320/3

= 440/1

= 440 

Hope this helps! 

Related Questions

4/5 os the fourth multiple of what unit fraction?
the castle is in the shape of a rectangular prism. the length is 25 feet the width is 157 feet and the height is 38 feet. what is the surface area of the castle? what is the volume of the castle?
What is 7x8 and 9x2 and 7555x90
Bobby made cookies. The circumferences of cookies are 6 cm. What is the diameter of the cookies?
How do I solve this complex multi-step equation 2x + (-2 )= 10x - 4 ?

Y= 3x - 10
y= 2x - 5

Answers

The solution to the system of equations is x = 5 and y = 5. The coordinates (5, 5) represent the point where the two lines intersect in the xy-plane, and it is the unique solution to this system of linear equations.

Given that the system of equations:

y = 3x - 10                                     (1)

y = 2x - 5                                       (2)  

Since both equations are set equal to y, equate the right-hand sides of the equations since they represent the same value of y:

3x - 10 = 2x - 5

Now, let's solve for x:

3x - 2x = -5 + 10

x = 5

Now, found the value of x, substitute it back into either of the original equations to find the corresponding value of y.

Let's use the equation (1):

y = 3x - 10

y = 3(5) - 10

y = 15 - 10

y = 5

Hence, the values of x and y are 5 and 5. The system of equations have unique solution.

Learn more about Linear equation here:

brainly.com/question/32634451

#SPJ3

Complete question:

Solve the system of equations for x and y:

y= 3x - 10\ny= 2x - 5


If you're looking for a solution for both equations and had a choice between the 3 ways of solving it, I would choose substitution for this problem. So..

2x-5=3x-10

Move like terms to their own sides.

Take 2x away from both sides, and add 10 to both sides. That should leave you with

5=x

Now that you have the x, plug it into the equation that works best for you to solve.

That should be y=2(5)-5

y=10-5

y=5

(5,5) is your solution.

If h(x)=(fog)(x) and h(x)=³√x+3, find g(x) if f(x) =³√x+2

Answers

Answer:

g(x)=x+1

The problem:

Find g(x) if h(x)=(f \circ g)(x),

h(x)=\sqrt[3]{x+3}, and

f(x)=\sqrt[3]{x+2}.

Step-by-step explanation:

h(x)=(f \circ g)(x)

h(x)=f(g(x))

Replace x in f(x)=\sqrt[3]{x+2} with g(x) since we are asked to find f(g(x)):

\sqrt[3]{x+3}=\sqrt[3]{g(x)+2}

\sqrt[3]{x+1+2}=\sqrt[3]{g(x)+2}

This implies that x+1=g(x)

Let's check:

(f \circ g)(x)

f(g(x))

f(x+1)

\sqrt[3]{(x+1)+2}

\sqrt[3]{x+1+2}

\sqrt[3]{x+3}  which is the required result for h(x).

Yunika downloaded three applications for $2.99 each to her cell phone. The remaining applications that Yunika purchased cost $1.99 each.If she downloaded x total applications, which of the following equations can be used to find how much Yunika spent on cell phone application downloads?

Answers

Answer:

The answer is A. y = 1.99(x - 4) + 11.96

Step-by-step explanation:

I just took the quiz.

You can formulate the equation below to work out your question:

3(2.99) + 1.99(x-3) 
8.97 + 1.99x - 5.97
1.99x + 3 

CHECK:
If x = 5
3 x 2.99 + 2 x 1.99 = 8.97 + 3.98 = 12.95
1.99 x 5 +3 = 12.95

Hope I helped.

Compare using or8. 6 pints60 fluid ounces10. 5 quarts20 cups

Answers

6pints>60 fluid ounces 
5quarts= 20cups

Which two steps should be used first in solving the system of equationsby substitution?
6y - 4x = 22
y + 2x = 9
A. Multiply the first equation by 4 and the second equation by 2.
B. Solve the second equation for y and then substitute this value into the first
equation.
C. Subtract the terms in the second equation from the first equation and then
solve for y.
D. Substitute 9 for y in the first equation and then solve the other equation for x.

Answers

Answer:

The value of x , y  using substitution method is 2 , 5

Step-by-step explanation:

Given as :

The two linear equation as

6 y - 4 x = 22            .......1

y + 2 x = 9                

Let y = 9 - 2 x             .......2

Now, using substitution method

Substitute the value of y from eq 2 into eq 1

i.e 6 × (9 - 2 x) - 4 x = 22

Or, 54 - 12 x - 4 x = 22

Or, 12 x + 4 x = 54 - 22

Or, 16 x = 32

∴  x = (32)/(16)

i.e x = 2

Now, Put the value of x into eq 2

∴ y = 9 - 2 x

So, y = 9 - 2 × 2

Or, y = 9 - 4

i.e y = 5

So, The value of x , y = 2 , 5

Hence, The value of x , y  using substitution method is 2 , 5   Answer

Answer:

first step :  option B

second step :  option D

Step-by-step explanation:

  • first,  Solve the second equation for y and then substitute this value into the first  equation.
  • after this, you will get the value of y then substitute this value in of the equations to get x.
  • so, option B will be the first step to solve and option D is the second step.
  • the other two steps are wrong.
  • this is a standard way to solve any 2 given equations with 2 variables.

Find the mean of 11,-7,-14,10,-5

Answers

The mean to your question is -1. What you do is: 1) add all numbers together. 2) divide the sum by the amount of numbers in the question which is 5. 3) you get -1 as your mean. Hope this helps!

Final answer:

The mean of the numbers 11,-7,-14,10,-5 is found by adding all the numbers together, and then dividing by the number of numbers. In this case, the mean is -1.

Explanation:

To find the mean of the numbers 11,-7,-14,10,-5, you'll want to add all of these numbers together then divide by the amount of numbers there are. This is because the mean is the average value of a set of numbers.

First, add up all your numbers: 11 + -7 + -14 + 10 + -5, which totals to -5. There are 5 numbers in the set, so to find the mean, you then divide -5 by 5, which equals -1. So, the mean of the set of numbers 11, -7, -14, 10, -5 is -1.

Learn more about Mean here:

brainly.com/question/35447441

#SPJ2